Atypical Presentation of a Cellular Neurothekeoma On the Nasal Vestibule of a Pregnant Woman. (June 2016) - Song, Jin Soo A; Bullock, Martin Joseph; Hart, Robert; Trites, Jonathan; Rigby, Matthew; Taylor, S Mark
Neurothekeomas are rare benign solitary tumours of the skin, most commonly manifesting in the head and neck and upper extremities of adults within the second to third decade of life, more often appearing in females at a 2:1 ratio. The authors describe a case of an immunohistochemical diagnosis of a cellular neurothekeoma on the nasal vestibule of a pregnant woman, and discuss the curative ability of surgical excision in these patient cohorts.